7(x+3)-6=-8(x-6)

Simple and best practice solution for 7(x+3)-6=-8(x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x+3)-6=-8(x-6) equation:


Simplifying
7(x + 3) + -6 = -8(x + -6)

Reorder the terms:
7(3 + x) + -6 = -8(x + -6)
(3 * 7 + x * 7) + -6 = -8(x + -6)
(21 + 7x) + -6 = -8(x + -6)

Reorder the terms:
21 + -6 + 7x = -8(x + -6)

Combine like terms: 21 + -6 = 15
15 + 7x = -8(x + -6)

Reorder the terms:
15 + 7x = -8(-6 + x)
15 + 7x = (-6 * -8 + x * -8)
15 + 7x = (48 + -8x)

Solving
15 + 7x = 48 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
15 + 7x + 8x = 48 + -8x + 8x

Combine like terms: 7x + 8x = 15x
15 + 15x = 48 + -8x + 8x

Combine like terms: -8x + 8x = 0
15 + 15x = 48 + 0
15 + 15x = 48

Add '-15' to each side of the equation.
15 + -15 + 15x = 48 + -15

Combine like terms: 15 + -15 = 0
0 + 15x = 48 + -15
15x = 48 + -15

Combine like terms: 48 + -15 = 33
15x = 33

Divide each side by '15'.
x = 2.2

Simplifying
x = 2.2

See similar equations:

| 3(0.6+2n)+3.2=7.6 | | 60-11=x | | 3x^2+4x-4.75=0 | | 9=6x-10 | | 4+3(b+4)=-5(2b-11) | | 4.3-1.4(y+7)=-9.7 | | 4w^4+16w^2+15= | | 2(a-8)=-22+2a | | x+22=37.5 | | 5=6x-10 | | 4=6x-10 | | 3x=12.4 | | 22-4d=38 | | -10x^2-11x-3=0 | | 8(1+7x)=8-5x | | 2(b+3)=18 | | 4x^2-9=-16x | | 9(x+4)-2(3x-1)=50 | | -20=5g | | 2(7+7x)=14-x | | 2(3n+6)=3(12-2n) | | 3(4+x)=2x-5 | | 3m-11.5=4.2 | | -11=v+13 | | 2.4(b-3)+3.8=-8.2 | | 7y=43 | | 1841.6728=2*232.2344+l | | 2.5p+5=20 | | y+9=24 | | 2b-8=30 | | -30=f-2 | | 3(5+4)-x=20 |

Equations solver categories